Countering the counterfeiters - Venkataraman, Ray R.; Pinto, Jeffrey K. (Los Angeles, CA : SAGE Publications, Inc., 2017)
This case describes the negative impacts of counterfeiting in the health care industry. The costs of local supplier counterfeiting must be taken into account when manufacturers make location decisions in developing their overseas supply chain. The case illustrates the complexity in making global location planning decisions.
Originally published in Venkataraman, R. R., & Pinto, J. K. (2017). Countering the counterfeiters. In Operations management: Managing global supply chains (pp. 293-294). Thousand Oaks, CA: SAGE Publications. ISBN: 9781506302935.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Health facilities -- Business management; Health facilities -- Risk management; Industrial location; Regional planning; Counterfeits and counterfeiting